Entrepreneurship, innovation and sustainable growth - Asgary, Nader H.; Maccari, Emerson A. (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Entrepreneurship and innovation play a vital role in fostering sustainable development. Advances in technology and communications have both transformed the process of business as well as strengthened the role of entrepreneurship in developed and developing countries. This important book is the first to provide the fundamental concepts and applications for faculty and students in this field, and also serves as a professional reference for practicing entrepreneurs and policymakers. Each chapter provides a clear guide to the conceptual and practical elements that characterise entrepreneurship and the process of new venture formation, including functional strategies in key areas such as marketing, information technology, human resources management, and accounting and finance. Questions and exercises are presented throughout in order to encourage discussion and problem-solving. A quick summary of the important concepts and definitions are also provided. Keeping practicality as the book's core aim, all chapters include a long case study to set the scene and then draw upon shorter cases from both developing and developed countries to reinforce key learning objectives and the real-world application of the book's core concepts"--
OCLC-licensed vendor bibliographic record.
Keywords: Entrepreneurship; Sustainable development; Technological innovations -- Economic aspects; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Business Ethics; BUSINESS & ECONOMICS / Entrepreneurship